HUBUNGAN DUKUNGAN ORANG TUA DENGAN KARAKTER TOLERANSI SISWA MADRASAH IBTIDAIYAH - Siti Faizah Widyaningsih; Arif Wiyat Purnanto; Putri Meinita Triana; Heti Mirawati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this research is to investigate the relationship between parental support and tolerance character among fifth-grade students at MI An Nuur Cahaya Umat. The issue at MI An Nuur Cahaya Umat indicates that the level of tolerance is still low. The subjects of this study consisted of 18 students. Data collection technique used a questionnaire. The data analysis technique employed was Pearson Product Moment with the assistance of IBM SPSS-26. The research findings indicate that the Pearson Correlation result is 0.145, which is categorized as low, with a significance result of 0.566, indicating a low correlation between parental support and tolerance character. Therefore, it can be concluded that parental support correlates lowly with the tolerance character of fifth-grade students at MI An Nuur Cahaya Umat.